Proposal for the standardization of ﬂow cytometry protocols to detect minimal residual disease in acute lymphoblastic leukemia - Ikoma,Maura Rosane Valério (2015)
ABSTRACT Minimal residual disease is the most powerful predictor of outcome in acute leukemia and is useful in therapeutic stratiﬁcation for acute lymphoblastic leukemia protocols. Nowadays, the most reliable methods for studying minimal residual disease in acute lymphoblastic leukemia are multiparametric ﬂow cytometry and polymerase chain reaction. Both provide similar results at a minimal residual disease level of 0.01% of normal cells, that is, detection of one leukemic cell in up to 10,000 normal nucleated cells. Currently, therapeutic protocols establish the minimal residual disease threshold value at the most informative time points according to the appropriate methodology employed. The expertise of the laboratory in a cancer center or a cooperative group could be the most important factor in determining which method should be used. In Brazil, multiparametric ﬂow cytometry laboratories are available in most leukemia treatment centers, but multiparametric ﬂow cytometry processes must be standardized for minimal residual disease investigations in order to offer reliable and reproducible results that ensure quality in the clinical application of the method. The Minimal Residual Disease Working Group of the Brazilian Society of Bone Marrow Transplantation (SBTMO) was created with that aim. This paper presents recommendations for the detection of minimal residual disease in acute lymphoblastic leukemia based on the literature and expertise of the laboratories who participated in this consensus, including pre-analytical and analytical methods. This paper also recommends that both multiparametric ﬂow cytometry and polymerase chain reaction are complementary methods, and so more laboratories with expertise in immunoglobulin/T cell receptor (Ig/TCR) gene assays are necessary in Brazil.